Ermittlung der tageszeitlichen Parkraumnachfrage. Ein innovatives Verfahren mit Differenzierung der Nutzergruppen. - Bergmann, Ulrich; Frewein, Markus (Deutscher Verkehrs-Verl., 2004)
So wie Wirtschaftsbetriebe Marktforschung für ihre Produkte betreiben, sollten auch Kommunen bereit sein, Angebot und Nachfrage nach Stellplätzen kritisch zu hinterfragen. Der Parkplatz im öffentlichen Straßenraum kann als Dienstleistung der Stadtverwaltung angesehen werden und ist gleichzeitig auch Steuerungselement im städtischen Verkehrssystem. Voraussetzung für die Steuerung der zeitlichen und örtlichen Verfügbarkeit ist die Kenntnis tageszeitlicher Parkraumnachfrage unterschiedlicher Nutzergruppen. difu

Local authorities ought to be prepared to review the demand for, and availability of, car parking space. One of the essential preconditions for controlling time limited - and locally available - space is awareness of different user groups' demand during the day. The innovative Bergmann/Frewein Method 2003 makes it possible to ascertain parking space demand levels at given times of the day. It was developed as part of an investigation into car parking in Steyr. The existing methods to assess demand have relied solely on selected data, which has not allowed taking into account local conditions or any known user behaviour. This innovative method facilitates the creation of modules based on comprehensive empirical traffic data and incorporates theory-based aspects of parking habits related to demand changes of different user groups during the day. difu
Keywords: Stadtverkehr; Innenstadt; Individualverkehr; Autoverkehr; Parken; Stellplatz; Nutzer; Nachfrageentwicklung; Befragung; Parkraum; Tageszeit; Parkraumbewirtschaftung; Planungsgebiet